Entre a escola e a sociedade: bases para a formação continuada de professores de Geografia na perspectiva da inclusão escolar de estudantes com baixa visão e cegos, em Uberlândia-MG - Almeida, Diones Carlos de Souza (2011)
The 1990 s in Brazil is considered a landmark on the Education for All. Since then, the education of students with special educational needs has been a fashionable topic of educational public policies. These policies reflect the neoliberal logic, overcoming the economic to the social. So, the state has responded minimally to the needs and aspirations of the education sector, so it s possible to consider the existence of an Inclusion in reverse . In other words, it is ensured the right to equal access to education, but there are no effective conditions for the permanence of these students in the teaching and learning process. This fact becomes more significant when the target public are people with disabilities (physical, intellectual, sensory or multiple). Indeed, the school inclusion is a movement that has demanded definition in practical order, both in infrastructural and organizational level. Therefore, we can notice the mismatch between the educational legislation and the real conditions of practicability of the project, given the current landscape of the Brazilian educational system. There are several inconsistencies; for example, the idea that Inclusive Education and Special Education are contradictories. There is consensus, however the need to (re)consider the teacher training, promoting the transformation of traditional educational practices for education to be accessible to all, but also having quality. In this context, this research aims at knowing the continued education of the Geography teacher in Uberlândia- MG in the face of new requirements imposed by public policy in the context of School Inclusion of People with Visual Handicap. The data reveals: considering the twenty four institutions of support/assistance/education in the area of Visual Handicap (10 are municipal schools and 08 are state schools), we can infer that in spite of the difficulties observed, municipal reality is relatively more structured than the state education system, especially when we consider the work of the Specialized Educational Assistance (SEA) in Multifunctional Resource Classrooms. Also, we can say that the main obstacle in the context of inclusive education is due to the existence of crystallized educational and social practices. It still remains the idealized conception of students as subjects whose individuality is not respected and, above all, valued. Therefore, knowledge areas traditionally valued in the mainstream school have been reproduced in the processes of schooling people with disabilities, limiting diverse experiences of teaching and learning.